A dimensão estratégica das práticas de responsabilidade social - Gurgel, Adrômida Marrali Silva Cortêz (2015)
This research has as object of study a mall opened in 2005 has 67 million square feet of gross leasable area and currently generates 6,500 direct and indirect jobs. An approach about theories of social and environmental corporate responsibilities focused on the competitive advantage and value creation organizational image was made. This study seeks to identify whether the perception of direct and indirect customers of the organization's social responsibility actions constitute a factor of differentiation. It is an explanatory and exploratory research, as qualitative and quantitative data are addressed with the content analysis of the interviews applied to shopping managers researched and medium tests and analysis of frequency data collected by questionnaires from the shopkeepers customers and end users / buyers/visitors. The results showed that the managers interviewed have social actions taken by shopping as tools that benefit society and at the same time generate benefits for the organization's image. Since the social responsibility of the company searched seek generate benefits its image before the society in which is inserted and its direct and indirect customers, the result of this research positively supports the differentiation strategy of this company, because the direct and indirect customers samples surveyed, mostly perceive the existence of social and environmental responsibility actions taken by shopping and have them as extremely important